Combination of Metagenomics and Culture-Based Methods to Study the Interaction Between Ochratoxin A and Gut Microbiota - Guo, Mingzhang (Toxicol Sci, 2014)
Gut microbiota represent an important bridge between environmental substances and host metabolism. Here we reported a comprehensive study of gut microbiota interaction with ochratoxin A (OTA), a major food-contaminating mycotoxin, using the combination of metagenomics and culture-based methods. Rats were given OTA (0, 70, or 210 μg/kg body weight) by gavage and fecal samples were collected at day 0 and day 28. Bacterial genomic DNA was extracted from the fecal samples and both 16S rRNA and shotgun sequencing (two main methods of metagenomics) were performed. The results indicated OTA treatment decreased the within-subject diversity of the gut microbiota, and the relative abundance of Lactobacillus increased considerably. Changes in functional genes of gut microbiota including signal transduction, carbohydrate transport, transposase, amino acid transport system, and mismatch repair were observed. To further understand the biological sense of increased Lactobacillus, Lactobacillus selective medium was used to isolate Lactobacillus species from fecal samples, and a strain with 99.8% 16S rRNA similarity with Lactobacillus plantarum strain PFK2 was obtained. Thin-layer chromatography showed that this strain could absorb but not degrade OTA, which was in agreement with the result in metagenomics that no genes related to OTA degradation increased. In conclusion, combination of metagenomics and culture-based methods can be a new strategy to study intestinal toxicity of toxins and find applicable bacterial strains for detoxification. When it comes to OTA, this kind of mycotoxin can cause compositional and functional changes of gut microbiota, and Lactobacillus are key genus to detoxify OTA in vivo.